Evaluation of drinking water quality in Lake Mzingazi in Richards Bay. - Mathenjwa, Cleopas Mzondeni. (2009)
Introduction Lake Mzingazi is the only suitable source of domestic water supply for the Richards Bay community. Rapid industrialisation in the city of uMhlathuze, accompanied by an influx of people, has resulted in informal settlement occurring around the lake. The uncontrolled activities of this development threaten to pollute the water source. Previous studies in1979 conducted by Council of Scientific & Industrial Research indicated that Lake Mzingazi water was still within acceptable limits in terms of the Department of Water Affairs & Forestry guidelines. The lake water quality was that of a Class I water resource, which is excellent for domestic use. Pollution of the lake can result from diffuse sources of pollution due to settlement of communities around it. Water purification costs could escalate thus forcing an increase in water tariffs. If pollution resulted in the lake being unable to be utilized, the Richards Bay community will be seriously affected, as it would necessitate the importing of water from distant regions. Either way, the expense of acquiring water would increase. All living organisms rely on adequate water for their survival. Worse still are human beings for their water should not only be adequate but should be of good quality to prevent health risks and even death. It is in view of these possibilities that the study was undertaken. Aim The aim of the study is to assess the extent of physical, chemical and biological pollution in Lake Mzingazi due to non-point sources and to recommend necessary protection measures that need to be implemented to prevent any negative health impact on surrounding communities. At present there are no restrictions and no protection of the lake from pollution except that no recreation is allowed into the lake at present. Methods Several objectives were set in order to focus on specific issues. One of the objectives was to inform the communities around the lake about the study. Sampling of the lake water was conducted monthly from June to November 2006 (using a boat). Pictures of areas around the lake were also taken for further analysis. At each sampling run, 36 samples were taken and delivered to a laboratory accredited by the South African National Accreditation Standards for analyses. Six sampling runs were completed. Secondary data for the period of 1998 to 2005 were obtained from uMhlathuze Municipality in order to establish pollution trends and for comparison purposes with the Department of Water Affairs and Forestry guidelines. Results The findings of the study revealed that the quality of the lake water is still within acceptable limits when compared with the Department of Water Affairs & Forestry guidelines; however, informal settlement threatens the future of the lake by encroaching into the lake banks. Discussion There is definitely a risk of pollution to Lake Mzingazi as long as there are no pollution prevention plans in place. Recommendations All data should be stored in a centralized information system to avoid losing valuable information. The Water Services Authority must develop and maintain a water quality-monitoring programme that will capture all changes occurring in the lake. === Thesis (MMed.)-University of KwaZulu-Natal, Durban, 2009.